’Terminativo’ vs ’no terminativo’: entre oposiciones y ambigüedades tempo-aspectiiates (el caso de las préteritos) - Nowikow, Wiaczesław (Studia Romanica Posnaniensia, 2003)
The aim of this paper is to specify the properties 'terminative' and 'non-terminative' in their relation to grammatical categories Preterite and Imperfect Tenses in Spanish and Perfective and lmperfective Aspects in Polish. The authour introduces the distinction between 'temporal delimitation' and process conclusion'. The latter implies the first one, but this relation doesn't function „the other way round".